2018
DOI: 10.18632/oncotarget.v9i27
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cytosolic DNA sensors are a subgroup of pattern recognition receptors (PRRs) and are activated by the abnormal presence of the DNA in the cytosol. Their activation leads to the upregulation of pro-inflammatory cytokines and chemokines and can also induce cell death. The presence of cytosolic DNA sensors and inflammatory cytokines in TS/A murine mammary adenocarcinoma and WEHI 164 fibrosarcoma cells was demonstrated using real time reverse transcription polymerase chain reaction (RT-PCR), western blotting and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…9 In a Swedish cohort of cervical cancer patients, HPV16, 18, 31, 45, and 33 were the most frequently detected genotypes. 28 In this epidemiological study, we found that HPV16 (22.7%), HPV52 (15.5%), HPV58 (14.6%), HPV81 (12.9%), and HPV53 (11.0%) were the common genotypes of HPV infections in HPV-positive cervical cancer patients. Further, our epidemiological study showed that HPV53 accounted for a high proportion of infection in both HPV-positive female patients and HPV-positive cervical cancer patients.…”
Section: Discussionmentioning
confidence: 72%
“…9 In a Swedish cohort of cervical cancer patients, HPV16, 18, 31, 45, and 33 were the most frequently detected genotypes. 28 In this epidemiological study, we found that HPV16 (22.7%), HPV52 (15.5%), HPV58 (14.6%), HPV81 (12.9%), and HPV53 (11.0%) were the common genotypes of HPV infections in HPV-positive cervical cancer patients. Further, our epidemiological study showed that HPV53 accounted for a high proportion of infection in both HPV-positive female patients and HPV-positive cervical cancer patients.…”
Section: Discussionmentioning
confidence: 72%
“…This single-arm pilot study was designed to determine the ORR of anti-PD-L1 (durvalumab) and anti-CTLA-4 (tremelimumab) in metastatic ER-positive BC and TNBC. 60 higher rates of clinical benefit were observed in TNBC. Further research is warranted in TNBC to confirm the findings.…”
Section: Dual Checkpoint Blockade Therapymentioning
confidence: 97%